IMPROVING STUDENTS™ COMPREHENSION IN READING REPORT TEXT BY USING CONTEXT CLUES TECHNIQUE - Maysarah, Fitri; -, Rahmah (TRANSFORM: Journal of English Language Teaching and Learning, 2013)
Abstract The objective of this research is to improve students™ comprehension in reading report text by using context clues technique. This study was conducted by using classroom action research. The subject of the research was class IX “ 1 in SMPN 1 Binjai which consisted of 23 students. The research covered two cycles and each cycle consisted of three meetings. Based on multiple choice test results, students™ scores kept improving in every test. The mean score of the first meeting test in first cycle was 60.87, the mean score of the third meeting test in first cycle was 74.35, and the mean score of the third meeting test in second cycle was 94.35. Based on dairy notes, observation sheet, questionnaire sheets and interview record, it was found that the quality of teaching-learning process ran well and influenced students™ courage and understanding in reading. Students were active and interested in learning process. They confidently figured out meanings of words and sentences by themselves through thinking process in order to gain comprehension. The research result showed that using Context Clues Technique could improve students™ comprehension in reading report text. Keywords: Comprehension, Reading, Report, Context Clues Technique